共同希望语言学院学生对汉语数字成语理解程度分析 - Sandy Riyadi (Sinolingua: Journal of Chinese Studies, 2025)
The research title of this article is “An Analysis of Students' Understanding of Chinese Numerical Idioms at the Common Hope Language Institute”. This article explores the comprehension and usage of Chinese numerical idioms among students at the Common Hope Language Institute, aiming to identify challenges and propose effective teaching strategies. Surveys and tests were used to assess students’ understanding and application of these idioms. Results indicate that while students show interest in numerical idioms, their comprehension is limited, with many struggling to grasp meanings and usage. Self-directed learning was found to play a critical role in enhancing idiom mastery, while general Chinese proficiency did not significantly influence performance. The study emphasizes the importance of incorporating idiom-focused teaching strategies, such as contextual exercises and activities encouraging independent learning, to address gaps in comprehension and practical usage. This research provides insights into the learning process of Chinese numerical idioms and offers actionable recommendations for improving teaching methods to support student success.